INCLUSION EDUCATION IN BANYUWANGI DISTRICT: STAKEHOLDER UNDERSTANDING AND BARRIERS TO IMPLEMENTATION - Zidniyati, Zidniyati; Faizah, Kurniyatul; Najamudin, Atho’ilah Aly; Rofiq, Ainur; Hidayati, Emi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article examines how minority students form and assert their identities in school's public spaces, particularly in interactions with majority groups. This qualitative research uses interviews and documentation studies, focusing on several minority students in schools in East Java. The research results show that the identity of minority students is formed through religious expressions, which include verbal expressions, attitudes of prayer, and greetings on holidays. These three expressions function as a means for minorities to assert their identity among the majority. This research concludes that identity formation depends on significant religious expressions and small actions carried out repeatedly. Therefore, schools must provide equitable social spaces for minority students, with policies supporting equality and respecting differences in school social life. The research results show that the understanding of inclusive education is still limited to involving children with special needs in regular school learning classes. Significant structural and cultural obstacles exist to its implementation, and inclusive education needs to be redefined to make it more holistic. This research produced recommendations, including improving infrastructure, training teaching staff, and developing policies that support inclusive education. The findings from this research illustrate the importance of a broader understanding of inclusive education and the need for strategic action to ensure equal access to education for all children.